In-season Phosphorus Dynamics in Rice-Wheat Cropping System Under Long-Term Fertilizer Management in an Inseptisol of North India - Ajay Sharma (Journal of the Indian Society of Soil Science, 2023)
The present study aimed to investigate the effects of long-term nutrient management practices on in-season inorganic phosphorus (P) transformations in rice-wheat system. The ongoing long-term fertilizer experiment at Research Farm, Department of Soil Science, Punjab Agricultural University, Ludhiana was selected to conduct the present study. The treatments comprised of combination of chemical fertilizers (100% NPK and 150% NPK) and organic manures (100% NPK+FYM, 100% NPK+GM and 100% NPK+Straw Incorporation) along with unfertilized control laid out in a randomized complete block design. In-season (30, 60, 90 and 120 DAT/DAS and at harvest of rice and wheat, respectively) soil samples were collected and analyzed for saloid-P (Sa-P), aluminium-P (Al-P), iron-P (Fe-P) and calcium-P (Ca-P). Plant samples were also collected at corresponding periods to determine the P content, uptake and biomass. Different fertilizer combinations and crop growth periods influenced the soil P dynamics and uptakes. Higher Sa-P, Al-P, Fe-P and Ca-P were recorded under FYM integrated treatments during all rice and wheat growth periods. Among the inorganic P fractions, Ca-P was most dominant and followed the sequence: Ca-P > Al- P > Fe-P>Sa-P. After 19 years of cropping cycle, high build-up of P in soil under various fractions was noticed under the application of chemical and integrated fertilizer management compared to control. The maximum concentration of Ca-P in the present study indicates that the supply of P in alkaline soils is controlled by this fraction which remains in equilibrium with Sa-P.